2012
DOI: 10.1007/s00244-012-9771-6
|View full text |Cite
|
Sign up to set email alerts
|

High Exposure Rates of Anticoagulant Rodenticides in Predatory Bird Species in Intensively Managed Landscapes in Denmark

Abstract: The extensive use of anticoagulant rodenticides (ARs) for rodent control has led to widespread secondary exposure in nontarget predatory wildlife species. We investigated exposure rates and concentrations of five ARs in liver samples from five raptors and six owls from Denmark. A total of 430 birds were analysed. ARs were detected in 84-100 % of individual birds within each species. Multiple AR exposure was detected in 73 % of all birds. Average number of substances detected in individual birds was 2.2 with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 26 publications
5
54
1
Order By: Relevance
“…macroscopic haemorrhages with no trauma) have been statistically characterised as representative of a high-risk toxic threshold [84]. According to these criteria, hepatic concentrations above 0.2 mg/kg have been associated with mortalities in raptors and small mustelids from Denmark [85], in raptors and hedgehogs from Mediterranean region of Spain [86], in six raptor species from Canary Islands, Spain [77].…”
Section: Wildlife Exposures and Intoxicationmentioning
confidence: 99%
“…macroscopic haemorrhages with no trauma) have been statistically characterised as representative of a high-risk toxic threshold [84]. According to these criteria, hepatic concentrations above 0.2 mg/kg have been associated with mortalities in raptors and small mustelids from Denmark [85], in raptors and hedgehogs from Mediterranean region of Spain [86], in six raptor species from Canary Islands, Spain [77].…”
Section: Wildlife Exposures and Intoxicationmentioning
confidence: 99%
“…Because of this increased persistence in animal tissues, especially in liver (Langford et al, 2013), the use of SGARs is associated with an increased risk of secondary poisoning for predators and scavengers feeding on contaminated rodents. Evidence of secondary poisoning was confirmed in predatory bird species such as barn owl (Tyto alba), buzzard (B. buteo), kestrel (Falco tinnunculus), Red kyte (Milvus milvus), and tawny owl (Strix aluco) (Christensen et al, 2012 ;Hughes et al, 2013 ;Geduhn et al, 2015), in predatory mammals such as red foxes (Vulpes vulpes) (Sage et al, 2010), European mink (Mustela lutreola) (Fournier-Chambrillon et al, 2004), weasels (Mustela nivalis) (Elmeros et al, 2011). Therefore, ARs were identified by the European Union as candidates for future comparative risk assessment and substitution in view of their unacceptable risk of secondary poisoning for wildlife.…”
Section: Introductionmentioning
confidence: 97%
“…Beside these low occurrences, it is important to consider that several recent specific studies found high exposure to anticoagulant rodenticides in liver tissues of the raptor species (Thomas et al 2011;Christensen et al 2012;Coeurdassier et al 2012;Hughes et al 2013). Moreover, we need to acknowledge our limits in correctly identifying the poisoning and debilitation cases, not having performed toxicological tests.…”
Section: Discussionmentioning
confidence: 99%